Rekomendasi Pemilihan Properti Kota Malang Menggunakan Metode AHP-SAW - Syafruddin Agustian Putra; Nurul Hidayat; Lailil Muflikhah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
The increasing of population number in Malang City triggered property developers to answer people's needs by developing and supplying assorted facilities of property. Many criterias should be considered by prospective buyers in selecting a property, for example: price, number of bedrooms, bathrooms, garages, building area, and land area. The numerous considerations referring to some specific criteria lead prospective buyers to take a difficult decision. Regarding to this problem, there are several methods able to resolve the complicacy of buyers in taking decision, which are performing combination of Multi Criteria Decision Making (MCDM) method by using Analytic Hierarchy Process (AHP) as a way to calculate weight of each determined criterion, and Simple Additive Weighting (SAW) as a method used in ranking the criteria. In functional test, the result of 100% represents that the system runs very well as designed. And from the accuracy test, the result is 80.80%. In sum, the AHP-SAW method combination is compatible to be used in selecting property in Malang City